Association between personality factors and health-related quality of life in type 1 diabetes patients - Gavazza,Maria Luiza Nogueira de Barreiros (2022)
ABSTRACT Objectives: The objective of the present study was to evaluate a possible association between personality factors (PF) and the health-related quality of life (HRQoL) of type 1 diabetes (T1D) patients. This allows for the investigation of obstacles related to treatment type and the presence of complications in HRQoL. Materials and methods: This cross-sectional study enrolled 78 patients aged 13-67 years from two diabetes clinics. PF was evaluated using the validated questionnaire Inventory of the Five Great Personality Factors. HRQoL was determined using the Brazilian Problem Areas in Diabetes Scale (B-PAID) questionnaire. The chi-square test, Fisher's exact test, and Welch's modified two-sample t-test were used to establish relationships. Results: In this sample of 46 women and 32 men with T1D and mean A1C of 8%-9%, we observed great suffering in 58.97% and that HRQoL was worse in women. “Openness” was the most prevalent PF and “extroversion” the least prevalent. “Neuroticism” facilitated a tendency to tolerate suffering. Conclusion: T1D patients’ personalities influence their treatment. The PF “neuroticism” is potentially related to better HRQoL. Brazilian T1D patients indicated great suffering in their HRQoL, which may be characteristic across the country. Women experienced worse HRQoL, which is in line with world literature. However, the limited sample size in this study warrant further research to test the hypotheses.